Die leksikografiese aanbieding en behandeling van vaste uitdrukkings - Gouws, Rufus H. (Lexikos, 2013)
The Lexicographic Presentation and Treatment of Fixed Expressions. In their decisions regarding the inclusion of fixed expressions in their dictionaries it is important for lexicographers to be familiar with the status of fixed expressions as fully-fledged lexical items. This status should have an influence on the way in which fixed expressions are presented and treated. With reference to the treatment allocated to fixed expressions in a few dictionaries it is argued in this paper that they should be awarded lemma status in dictionaries. It is proposed that fixed expressions should be included as sublemmata, presented in a nested text block that is attached to the article of a lemma representing a keyword from the fixed expression. Their treatment should be more comprehensive than what is currently found in prevailing general dictionaries. A focus on lexicographic functions demands the inclusion of certain item types in the treatment of fixed expressions. This includes etymological data as well as much more explicit guidance with regard to culture-bound lexical items. Keywords: cognitive function, contextual guidance, cotextual guidance, culture-bound items, fixed expression, guiding element, idioms, item, lemma sign, lemmatic addressing, lexicographic functions, lexicographic treatment, nest, niche, nonlemmatic addressing, partial article stretch, sublemma